The Influence of Liquidity, Leverage and Profitability Ratio on Finansial Distress: (On Real Estate and Property Companies Listed in Indonesia Stock Exchange in 2015-2017) - Fatimah Fatimah; Akhmad Toha; Aryo Prakoso (Politeknik Ganesha Medan, 2019)
This study investigates the role of the financial ratio in predicting financial distress which has an important role in preventing bankruptcy. This study aims to know the influence of liquidity, leverage, and profitability ratios on financial distress (on real estate and property companies listed in Indonesia Stock Exchange in 2015-2017). 45 companies listed in Indonesia Stock Exchange from 2015 to 2017 were examined by using 135 units of analysis. Prediction model used was logistic regression technique with purposive sampling method. The findings indicated that there was no influence of liquidity (current ratio) on financial distress. There was a positive influence of leverage (total dept. on total assets) on financial distress. However, there was a negative influence of profitability (net profit margin) on financial distress.